Handbook of affective sciences - Scherer, Klaus R.; Davidson, Richard J.; Goldsmith, H. Hill (London Oxford University Press, 2009)
This volume is a comprehensive roadmap to the burgeoning area of affective sciences, which now spans several disciplines. The Handbook brings together, for the first time, the various strands of inquiry and latest research in the scientific study of the relationship between the mechanisms of the brain and the psychology of mind.<U+000d><U+000a>In recent years, scientists have made considerable advances in understanding how brain processes shape emotions and are changed by human emotion. Drawing on a wide range of neuroimaging techniques, neuropsychological assessment, and clinical research, scientists are beginning to understand the biological mechanisms for emotions.
Keywords: Afectividad; Emociones